Kepraktisan E-Modul Disertai Mind Map pada Materi Protista Kelas X SMA/MA - Amri, Erismar; Rosba, Evrialiani; Marjani, Rizka (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to produce e-modules accompanied by mindmaps on Protista material for class X SMA/MA which is practical. This type of research is Research and Development (R&D) using the ASIE model, namely analyze, strategize, implement, and evaluate. The research subjects were 1 biology teacher and 18 students with a data collection instrument in the form of a practicality questionnaire. The results showed that (1) e-modules accompanied by mind maps that have been developed are very practical as evidenced by the percentage value of the practicality test by teachers in the aspect of ease of use of 96.67% with a very practical category, the aspect of learning time efficiency of 100% with a very practical category, and the benefit aspect of 100% with a very practical category. (2) e-modules accompanied by mind maps that have been developed are very practical as evidenced by the percentage value of the practicality test by students in the aspect of ease of use of 89.2% with a very practical category, the efficiency aspect of learning time of 84.95% with a very practical category, and the benefit aspect of 92.2% with a very practical category.